The distribution of income by sectors of the population - Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2000)
I interpret the distribution of income by sectors of the population to refer to the personal distribution of income, with evidence about it derived from household surveys. Section 1 outlines the links between the personal and factor income distributions, and includes a discussion of research using National Accounts data to check the quality of household survey income data. Section 2 provides a number of breakdowns of the personal income distribution in Britain using a variety of methods and subgroup types (including age, family type, housing tenure, and economic status). Section 3 draws attention to longitudinal issues how much individualss incomes and subgroup membership changes between one year and the next, and the links between them. Section 4 provides a summary and concluding remarks.
Keywords: 330